2017
DOI: 10.1002/jbm.a.36057
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to metal on polyethylene implants: Highly destructive lesions related to elevated concentration of cobalt and chromium in synovial fluid

Abstract: Adverse local tissue reactions (ALTR) are the primary cause of failure of metal on metal (MoM) hip implants, and fewer but not negligible number cases of nonmodular metal on polyethylene (MoP) implants. In this study, we analyzed 17 cases of MoP ALTR, and equal number of MoM, by histological observation, cobalt and chromium concentration in serum and synovial fluid and cytokine analysis in ALTR tissues. ALTRs in MoP are highly necrotic, affecting larger areas than MoM ALTRs. Degenerative changes in blood vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 33 publications
4
46
0
9
Order By: Relevance
“…XLPE acetabular liners are commonly used with metallic femoral heads in THR owing to their excellent in vitro and in vivo performance. However, many retrieval and case studies have shown that metal release from the taper‐trunnion junction of modular MoP THRs can cause an adverse reaction, leading to failure of the prostheses . This is the first long‐term hip simulator study to report material loss from the taper‐trunnion junction of the most commonly used bearing combination in hip prostheses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…XLPE acetabular liners are commonly used with metallic femoral heads in THR owing to their excellent in vitro and in vivo performance. However, many retrieval and case studies have shown that metal release from the taper‐trunnion junction of modular MoP THRs can cause an adverse reaction, leading to failure of the prostheses . This is the first long‐term hip simulator study to report material loss from the taper‐trunnion junction of the most commonly used bearing combination in hip prostheses.…”
Section: Discussionmentioning
confidence: 93%
“…Persson et al reported a 0.5% prevalence of revision surgery for ARMD after a mean follow‐up of 7 years in a one center observational cohort study of MoP THRs with the same Ti6Al4V femoral stems . Retrieval studies reported ARMD due to wear debris produced from the taper‐trunnion junction of modular MoP THRs . Furthermore, several case studies reported metal release due to fretting, corrosion, or both and associated pseudotumor formation after MoP THR .…”
Section: Introductionmentioning
confidence: 99%
“…Serum cobalt and chromium ion levels have been used to diagnose taper corrosion. Metal artifact reduction sequence MRI is an excellent diagnostic tool for evaluation of patients with elevated serum cobalt after MoP THA [11], [16], [17], [18]. In the present case, we used MoP articulation at the time of revision surgery and careful follow-up is required for MACC to occur.…”
Section: Discussionmentioning
confidence: 94%
“…A ceramic head could decrease corrosion products from MACC at the trunnion and taper interface. MACC occurred at the head-neck and neck-stem taper junction in which at least one of the components is fabricated from cobalt-chromium alloy [9], [16], [17]. The retained stem had no option of a titanium sleeve for the use of a new ceramic head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation